The invisibilization of health promotion in Australian public health initiatives. (18th July 2016) - O'Hara, Lily; Taylor, Jane; Barnes, Margaret
Abstract: The field of health promotion has arguably shifted over the past thirty years from being socially proactive to biomedically defensive. In many countries this has been accompanied by a gradual decline, or in some cases the almost complete removal of health promotion designated positions within Government health departments. The language or discourse used to describe the practice and discipline of health promotion is reflective of such changes. In this study, critical discourse analysis was used to determine the representation of health promotion as a practice and a discipline within 10 Australian Government weight-related public health initiatives. The analysis revealed the invisibilization of critical health promotion in favour of an agenda described as 'preventive health'. This was achieved primarily through the textual practices of overlexicalization and lexical suppression. Excluding document titles, there were 437 uses of the terms health promotion, illness prevention, disease prevention, preventive health, preventative health in the documents analysed. The term 'health promotion' was used sparingly (16% of total terms), and in many instances was coupled with the term 'illness prevention'. Conversely, the terms 'preventive health' and 'preventative health' were used extensively, and primarily used alone. The progressive invisibilization of critical health promotion has implications for the perceptions and practice of those identifying as health promotion professionals and for people with whom we work to address the social and structural determinants of health and wellbeing. Language matters, and the language and intent of critical health promotion will struggle to survive if its speakers are professionally unidentifiable or invisible.